Came to Stay for Good? Mobility Decisions of International Students in Germany from a Lifecourse Perspective - Glorius, Birgit (Raumforschung und Raumordnung | Spatial Research and Planning, 2016)
Against the background of demographic ageing in Germany, there are increasing attempts to attract high qualified labor force from abroad, and there is high interest to retain international students who graduate from German universities. Germany is an important destination country for international students, and the formal conditions for staying on and entering the labor market upon graduation were largely liberated during the past years. Survey results show a high interest for an extended stay in Germany among international students, but retention rates reveal that those intentions are only partly put into practice. This article investigates on this discrepancy. Using a qualitative case study, the attitudes, experiences and future plans of international students in Germany are analyzed focusing on possible intentions to stay for good. The analysis focuses on the question, how decisions to move or stay on are embedded in biographical status passages such as the transition from university to work life. The results show a strong impact of life cycle considerations with regards to future mobility decisions among the interviewees. Both previous and future migratory decisions are negotiated on the basis of a transnational action space, integrating rational argumentation as well as subjectivities and influences from peers and family members.
Keywords: Highly skilled migrants; Life cycle; Student migration; Stay decisions